Legal Analysis of the Authority of Regional Governments in the Management of Regional Public Hospitals with the Status of Regional Public Service Agencies (Blud) from the Perspective of State Administrative Law - Yusriyani Yusriyani; Widayati Widayati (UNISSULA Semarang, 2025)
Abstract. The development of the management of the Regional General Hospital is an effort by the government to overcome various problems that always arise in the management of government hospitals, namely the difficulty of predicting the service needs of the community and the need for resources to support them. The purpose of this study is to analyze and describe the authority of the regional government in the management of regional general hospitals with the status of Regional Public Service Agency (BLUD) from the perspective of state administrative law. To analyze and describe the weaknesses of the regional government in the management of regional general hospitals with the status of Regional Public Service Agency (BLUD) from the perspective of state administrative law. To analyze and describe efforts to overcome the weaknesses of the regional government in the management of regional general hospitals with the status of Regional Public Service Agency (BLUD) from the perspective of state administrative law. The method used by the researcher is a normative juridical research method, with the approaches used being a legislative approach and a conceptual approach. This research is prescriptive research. The data sources and types used in this study are secondary data obtained from literature studies. The data were analyzed qualitatively using welfare state theory, legal effectiveness theory, and authority theory. Based on the results of the study, the authority of regional governments in managing Regional General Hospitals (RSUD) with the status of Regional Public Service Agencies (BLUD) is rooted in the principle of regional autonomy, where regional governments have the right to organize government affairs, including health affairs. From the perspective of state administrative law, this authority includes planning, implementation, guidance, and supervision that are more flexible than ordinary SKPD, with the aim of improving the professionalism and quality of public services. This flexibility is especially in financial management, where BLUD RSUD is given leeway to implement healthy business practices for the sake of efficiency and effectiveness of services. The weaknesses of regional governments in managing RSUD with BLUD status, from the perspective of state administrative law, include the weakness of incompetent human resources, the lack of understanding of the regional bureaucracy regarding the essence of BLUD, the dynamics of official turnover that hinders sustainability, and limited internal control that can lead to the risk of opportunistic behavior. In addition, there are also obstacles beyond the direct control of regional governments such as the mistaken view that BLUD aims to seek commercial profits. Efforts to address regional government weaknesses in managing regional public hospitals (RSUD) and hospitals (BLUD) from a state administrative law perspective include increasing human resource capacity and understanding of BLUD regulations, improving financial governance and optimal use of information systems, and strengthening communication synergies between regional governments and hospitals. Furthermore, it is necessary to prepare supporting instruments such as operational guidelines, promote transparency and accountability, and implement principles of efficiency and entrepreneurship.